TRANSFER OF RIGHTS TO COLLECT (CESSIE) AND LEGAL CONSEQUENCES ON DEBITOR COLLATERAL ITEMS IN RESOLVING NON-PERFORMING CREDIT (Case study on Pekanbaru District Court Decision No. 129/Pdt.G/2016/PN.Pbr) - Hamler; Mirwati, Yulia; Yulfasni; Nurdin, Zefrizal (PENA LAW: International Journal of Law, 2024)
Banks can deal with negative credit by purchasing, selling, and transferring the rights to receivables (cessie). According to the District Court's ruling in case No. 129/Pdt.G/2016/ PN.Pbr, the lawsuit was filed by a cessionary who had acquired receivables from the troubled PT Bank Tabungan Negara (Persero) Tbk. The Receivables Sale Purchase Agreement and Transfer of Cessie are the two (two) Notarial Deeds that include the terms of the transfer of receivables. According to the ruling, the Pekanbaru District Court approved the transfer of Land Ownership Certificates that had been pledged as security for the debtor (cessionaris). The problem is stated as follows: 1. Can the sale and purchase of receivables and the transfer of claim rights (cessie) give buyers of cessie legal certainty? 2. What are the legal ramifications of the debtor's assurance in light of Pekanbaru District Court Decision Number 129/Pdt.G/2016/PN.Pbr? and the purpose of this study is to comprehend the problem's genesis and offer solutions. The research method used in this study is known as normative legal research (doctrinaire), and it entails research on legal principles, legal aspects, and law as it is conceptualized as norms or rules that apply in society. It also includes an analysis of both written and unwritten legal rules that exist and develop in society, and it makes use of secondary data derived from primary, secondary, and tertiary legal materials. It is clear from this study that the sale and purchase of receivables and the transfer of cessie do not terminate the credit agreement between the cedent and cessus; rather, it is a transfer and delivery of receivables from the cedent to the cessionaris, and the transfer of cessus collateral must be based on a ruling made through litigation at the local District Court. And in this case, the transfer of Cessie and the sale and purchase of receivables are legal and do not violate the terms of the agreement. The judges' panel also believes that since the Cessus guarantee is not secured by a mortgage, the Cessus collateral object may be used to repay the debt by reclaiming the cessionaris name. Neither of these situations violates the rights to the bedding described in Article 1154 of the Civil Code.